1999
DOI: 10.1073/pnas.96.14.7780
|View full text |Cite
|
Sign up to set email alerts
|

The γ-subunit rotation and torque generation in F 1 -ATPase from wild-type or uncoupled mutant Escherichia coli

Abstract: The rotation of the ␥-subunit has been included in the binding-change mechanism of ATP synthesis͞ hydrolysis by the proton ATP synthase (F O F 1 ). The Escherichia coli ATP synthase was engineered for rotation studies such that its ATP hydrolysis and synthesis activity is similar to that of wild type. A f luorescently labeled actin filament connected to the ␥-subunit of the F 1 sector rotated on addition of ATP.This progress enabled us to analyze the ␥M23K (the ␥-subunit Met-23 replaced by Lys) mutant, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 38 publications
4
103
3
Order By: Relevance
“…Combined genetic and biochemical studies suggested that the ␥ subunit amino-and carboxyl-terminal domains interact through longrange conformational transmission (9)(10)(11). The ␥ subunit rotation was indicated biochemically by the ␤͞␥ cross-linking (12) and movement of a probe covalently connected to the ␥ subunit (13), and confirmed finally by the continuous rotation of an actin filament connected to the ␥ subunit of the F 1 sector immobilized on a glass surface (14,15). As discussed (15), proton transport through F o should drive ␥ rotation, leading to the ␤ subunit conformational change that releases the product ATP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combined genetic and biochemical studies suggested that the ␥ subunit amino-and carboxyl-terminal domains interact through longrange conformational transmission (9)(10)(11). The ␥ subunit rotation was indicated biochemically by the ␤͞␥ cross-linking (12) and movement of a probe covalently connected to the ␥ subunit (13), and confirmed finally by the continuous rotation of an actin filament connected to the ␥ subunit of the F 1 sector immobilized on a glass surface (14,15). As discussed (15), proton transport through F o should drive ␥ rotation, leading to the ␤ subunit conformational change that releases the product ATP.…”
mentioning
confidence: 99%
“…The ␥ subunit rotation was indicated biochemically by the ␤͞␥ cross-linking (12) and movement of a probe covalently connected to the ␥ subunit (13), and confirmed finally by the continuous rotation of an actin filament connected to the ␥ subunit of the F 1 sector immobilized on a glass surface (14,15). As discussed (15), proton transport through F o should drive ␥ rotation, leading to the ␤ subunit conformational change that releases the product ATP. Reversibly, ATP hydrolysis should also drive ␥ rotation, which is transmitted to the F o sector for proton translocation.…”
mentioning
confidence: 99%
“…The first high-resolution X-ray structure of the F 1 sector from bovine heart mitochondria clearly showed that the three b subunits in F 1 have different catalytic site conformations (7). A series of single molecule studies (Table 1) on thermophilic Bacillus PS3 and the Escherichia coli enzyme established that the c subunit (8,9) and cec 10 (10-12) assembly in F 1 and F-ATPase (F O F 1 ), respectively, rotate relative to a stator assembly. Thus, the rotation of F-ATPase is coupled with continuous proton transport through a water channel formed from subunits a and c, which include proton translocating residues Arg and Asp (or Glu), respectively (3).…”
Section: Introductionmentioning
confidence: 99%
“…The initial direct and visual rotation is observed by using a fluorescent actin filament attached to γ subunit (Yasuda et al, 1998), which provides the direct convincing evidence of the rotation of the F 1 -ATPase motor. In addition, other researchers have also observed the rotation of the F 1 -ATPase motor (Omote et al, 1999;Nishio et al, 2002;Pänke et al, 2000). Further, Noji and Yasuda used small colloidal gold bead of 40 nm in diameter as the propeller to study the mechanism of stepping of the F 1 -ATPase motor with highspeed imaging (Yasuda et al, 2001).…”
Section: Introductionmentioning
confidence: 99%